A gallium niobium calcium tantalum silicate piezoelectric crystal material and its preparation method and use
By adopting gallium silicate niobium tantalum piezoelectric crystal material and preparing it using crucible drop method, the existing high-temperature piezoelectric crystal material has been solved, and the piezoelectric performance of the existing high-temperature piezoelectric crystal material is not ideal and the preparation cost is high, and the high resistivity and excellent piezoelectric performance are achieved at high temperatures, which are suitable for high-temperature piezoelectric sensors.
Patent Information
- Application Number
- CN202510112983.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-01-24
AI Technical Summary
The existing high-temperature piezoelectric crystal materials have poor piezoelectric performance at high temperatures and are relatively high in preparation costs, making it difficult to meet the needs of the field of high-temperature piezoelectric sensing.
Gallium silicate niobium tantalum piezoelectric crystal material (Ca3(Nb0.2Ta0.8)Ga3Si2O14) was prepared by crucible drop method, and the high-temperature piezoelectric properties of the crystal were optimized by the substitution of Nb5+ and Ta5+.
It realizes high resistivity and excellent piezoelectric properties at high temperatures, reduces the preparation cost, and is suitable for high-temperature piezoelectric sensors over 800℃.
Smart Images

Figure CN119553367B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of crystal growth and application, and specifically relates to a gallium niobium tantalum calcium silicate piezoelectric crystal material and a preparation method and application thereof. Background Art
[0002] The most widely used piezoelectric crystals are quartz crystals and lithium niobate crystals. However, since quartz crystals will produce a twin crystal structure at a temperature of 350°C, as the temperature continues to rise, the quartz crystal undergoes an α-β phase transition, resulting in the inactivation of the piezoelectric performance, which limits the application of quartz crystals in high-temperature environments. Lithium niobate crystals have low resistivity at high temperatures and have domain structures. They will undergo chemical decomposition at a certain temperature, and the high-temperature resistivity is too low, and the loss is too high, which restricts their application in the field of high-temperature piezoelectric sensing. Therefore, finding new high-temperature piezoelectric crystals has become one of the research directions of piezoelectric materials.
[0003] Lanthanum gallium silicate series crystals (La3Ga5SiO 14 , LGS) has attracted much attention in the field of high-temperature piezoelectric crystals in recent years. It has the advantages of no phase change reaction and no pyroelectric effect in the range from room temperature to melting point, large piezoelectric coefficient, and high electromechanical coupling coefficient. However, the resistivity of this series of crystals is low at high temperatures, which hinders its further application under high temperature conditions.
[0004] Among a series of lanthanum gallium silicate crystals, calcium tantalum gallium silicate (Ca3TaGa3Si2O 14 CTGS) crystals have become an important research direction due to their relatively high high temperature resistivity and high mechanical quality factor. However, their piezoelectric performance at high temperatures is still not ideal.
[0005] In addition, CTGS crystals are usually grown by the Czochralski method, but this method has the problem of high cost in large-scale production.
[0006] Therefore, finding a high-temperature piezoelectric crystal with high high-temperature resistivity, good high-temperature piezoelectric performance and low preparation cost is an urgent problem to be solved. Summary of the invention
[0007] The present invention is directed to the existing technology and provides a gallium niobium tantalum calcium silicate piezoelectric crystal material and a preparation method thereof and an application in the field of high-temperature piezoelectricity.
[0008] The first aspect of the present invention provides a piezoelectric crystal material of calcium niobium tantalum gallium silicate, wherein the chemical formula of the calcium niobium tantalum gallium silicate piezoelectric crystal is Ca3(Nb 0.2 Ta 0.8 )Ga3Si2O 14 , the crystal belongs to A3BC3D2O 14The invention relates to a tantalum-niobium crystal of the present invention. The space group of the crystal is P321, the unit cell parameters of the crystal are a = b = 8.1020Å~8.1025Å, c = 4.9785Å~4.9795Å, α=β= 90°, γ=120°, and the crystal has a non-centrosymmetric structure without phase transition, and niobium and tantalum jointly occupy the B site.
[0009] Optionally, the relative dielectric constant of the crystalline material at room temperature is Greater than 18, relative dielectric constant Greater than 24.60, piezoelectric constant d 11 Greater than 4.20 pC / N, electromechanical coupling coefficient at 600°C k 12 Greater than 12.90%, resistivity greater than 2.20×10 at 800℃ 7 Ω·cm;
[0010] in, represents the free dielectric constant in the X direction (110), represents the absolute dielectric constant, It represents the free dielectric constant in the Z direction (001).
[0011] The second aspect of the present invention provides a method for preparing a gallium niobium calcium tantalum silicate piezoelectric crystal material, wherein the gallium niobium calcium tantalum silicate piezoelectric crystal material is the gallium niobium calcium tantalum silicate piezoelectric crystal material according to any one of the first aspects above, and the preparation method comprises:
[0012] Step 1, preparing gallium niobium calcium tantalum silicate polycrystalline material;
[0013] Step 2, placing a calcium tantalum gallium silicate seed crystal at the bottom of the crucible, filling the polycrystalline material on top of the seed crystal and sealing the crucible;
[0014] Step 3, placing the crucible in a crystal growth furnace, raising the temperature in the crystal growth furnace to melt the polycrystalline material and the top of the seed crystal, completing the inoculation, and obtaining the inoculated material;
[0015] Step 4: Control the temperature gradient in the crystal growth furnace to decrease, so that the inoculated material is crystallized, kept warm, and cooled to obtain the gallium niobium tantalum calcium silicate piezoelectric crystal material.
[0016] Optionally, step 1 includes:
[0017] Mixing CaCO3, Nb2O5, Ta2O5, Ga2O3 and SiO2 to obtain a mixed material;
[0018] The mixed material is sintered once at 1000° C. to 1100° C., and cooled to obtain a first sintered product;
[0019] The first sintering product is crushed, ground, and pressed into blocks, and a second sintering is performed at 1200° C. to 1350° C. and cooled to obtain the gallium niobium tantalum calcium silicate polycrystalline material.
[0020] Optionally, the first sintering time is 12 hours to 20 hours, and the second sintering time is 24 hours to 40 hours.
[0021] Optionally, step 3 includes:
[0022] Placing the crucible in a crystal growth furnace, placing the portion of the crucible where the polycrystalline material is placed in the high temperature zone of the crystal growth furnace, and raising the temperature of the high temperature zone to a first melting temperature to melt the polycrystalline material to generate a polycrystalline material melt;
[0023] The portion of the crucible where the top of the seed crystal is placed is placed in the temperature gradient zone of the crystal growth furnace, and the temperature of the temperature gradient zone is raised to the second melting temperature to melt the top of the seed crystal, and the temperature is kept to complete the inoculation and obtain the inoculated material.
[0024] Optionally,
[0025] The step of raising the temperature of the high temperature zone to a first melting temperature to melt the polycrystalline material and generate a polycrystalline material melt comprises: raising the temperature of the high temperature zone to 1480° C. to 1490° C. within 10 hours to fully melt the polycrystalline material and overheating the polycrystalline material by 50° C. to 100° C., and keeping the temperature for 24 hours to 48 hours to melt the polycrystalline material and obtain a polycrystalline material melt;
[0026] The step of heating the temperature gradient zone to a second melting temperature to melt the top of the seed crystal, keeping the temperature, completing the inoculation, and obtaining the inoculated material comprises: heating the temperature gradient zone to 1380°C to 1390°C to melt the top of the seed crystal, keeping the temperature for 2 hours to 3 hours, completing the inoculation, and obtaining the inoculated material.
[0027] Optionally, step 4 includes:
[0028] The crucible is placed on the descending device of the crystal growth furnace, and the descending device is controlled to descend in the temperature gradient zone of the crystal growth furnace, so that the inoculated material in the molten state in the crucible is crystallized and then stops descending, heat preservation, and cooling to obtain the gallium niobium tantalum calcium silicate polycrystalline material.
[0029] Optionally, along the descending direction of the crucible, the temperature of the temperature gradient zone decreases according to a gradient of 30°C / cm to 50°C / cm, and the descending speed of the crucible is 6 mm / day to 10 mm / day;
[0030] The insulation condition is 1200°C to 1300°C for 1.0 hour to 2.0 hour;
[0031] The cooling condition is to gradually cool to room temperature at a rate of 30° C. / hour to 50° C. / hour.
[0032] Optionally, the chemical formula of the calcium tantalum gallium silicate seed crystal is Ca3TaGa3Si2O 14 Single crystal.
[0033] Optionally, the crucible may have a size of Φ9 × Φ25 × 100 mm.
[0034] The third aspect of the present invention provides a use of a gallium niobium calcium tantalum silicate piezoelectric crystal material, and the use of the gallium niobium calcium tantalum silicate piezoelectric crystal material in the preparation of piezoelectric crystal materials and sensor devices. The gallium niobium calcium tantalum silicate piezoelectric crystal material is a crystal material prepared by the preparation method of the gallium niobium calcium tantalum silicate piezoelectric crystal material described in any one of the first aspects or the gallium niobium calcium tantalum silicate piezoelectric crystal material described in any one of the second aspects.
[0035] Compared with the prior art, the present invention has the following characteristics:
[0036] 1. The method for preparing gallium niobium tantalum calcium silicate piezoelectric crystals of the present invention is a crucible descent method, which has the following characteristics: (1) It can realize crystal growth in a non-growth habit direction and flexibly meet different application requirements; (2) By customizing the shape and size of the crucible, it supports the growth of crystals of specific sizes; (3) The use of a closed crucible effectively prevents contamination by external impurities and volatilization of melt components, ensuring the purity and chemical consistency of the crystal; (4) Multi-station crystal growth improves production efficiency, reduces costs, and realizes mass production.
[0037] 2. Due to Nb 5+ With Ta 5+ Belong to the same group of elements and have similar chemical structures, so in the crystal structure Ta 5+ The position is easily affected by Nb 5+ Replaced by niobium gallium silicate calcium tantalum, thus forming a single crystal (hereinafter referred to as CNTGS). At the same time, due to the different electron layers and radii of the two, Nb 5+ After entering the crystal lattice, the lattice parameters of the crystal will change. This change will further affect the high-temperature piezoelectric properties of the CNTGS crystal, giving the crystal unique advantages and potential application prospects in high-temperature piezoelectric applications.
[0038] The test results show that as the temperature rises, the electromechanical coupling coefficient of the undoped calcium tantalum gallium silicate crystal (hereinafter referred to as CTGS) increases from 10.95% to 12.45%, while the electromechanical coupling coefficient of the calcium tantalum gallium silicate crystal CNTGS increases from 11.25% to 12.96%. This increase in the electromechanical coupling coefficient indicates that the piezoelectric properties of CNTGS crystals at high temperatures are better than those of undoped CTGS crystals. At the same time, the resistivity of CNTGS crystals at high temperatures was tested and analyzed, and it was found that at 800°C, its resistivity was 2.23×10 7 Ω·cm, which is comparable to the resistivity of CTGS crystal (2.40×10 7 Ω·cm), which shows that it has excellent high-temperature resistivity. Therefore, CNTGS crystal is a crystal material with significant advantages in high-temperature piezoelectric applications, especially suitable for high-temperature piezoelectric sensors with operating temperatures exceeding 800 ℃.
[0039] 3. Piezoelectric constant of gallium niobium calcium tantalum silicate piezoelectric crystal d 11 Greater than 4.20pC / N, relative dielectric constant Greater than 18, relative dielectric constant Greater than 24.60; at a high temperature of 800°C, the resistivity of the crystal is greater than 2.20×10 7 Ω·cm, higher than 10 6 Ω·cm. Therefore, CNTGS crystals have broad application prospects in high-temperature piezoelectric sensors with operating temperatures exceeding 800℃. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is a physical picture of the gallium niobium calcium tantalum silicate piezoelectric crystal prepared in Example 1 of the present invention.
[0041] Figure 2 The XRD pattern of the calcium gallium niobium tantalum silicate piezoelectric crystal prepared in Example 1 of the present invention, CNTGS is Ca3(Nb 0.2 Ta 0.8 )Ga3Si2O 14 Abbreviation for crystal; CTGS is Ca3TaGa3Si2O 14 Abbreviation for crystal.
[0042] Figure 3 The electromechanical coupling coefficient of the gallium niobium calcium tantalum silicate piezoelectric crystal prepared in Example 1 of the present invention is k 12 Curve diagram of temperature change, CNTGS is Ca3(Nb 0.2 Ta 0.8 )Ga3Si2O 14 Abbreviation for crystal; CTGS is Ca3TaGa3Si2O14 Abbreviation for crystal.
[0043] Figure 4 The resistivity of the calcium niobium gallium silicate piezoelectric crystal prepared in Example 1 of the present invention varies with temperature. CNTGS is Ca3(Nb 0.2 Ta 0.8 )Ga3Si2O 14 Abbreviation for crystal; CTGS is Ca3TaGa3Si2O 14 Abbreviation for crystal. DETAILED DESCRIPTION
[0044] The first aspect of the present invention provides a piezoelectric crystal material of calcium niobium tantalum gallium silicate, wherein the chemical formula of the calcium niobium tantalum gallium silicate piezoelectric crystal is Ca3(Nb 0.2 Ta 0.8 )Ga3Si2O 14 , the crystal belongs to A3BC3D2O 14 The invention relates to a tantalum-niobium crystal of the present invention. The space group of the crystal is P321, the unit cell parameters of the crystal are a = b = 8.1020Å~8.1025Å, c = 4.9785Å~4.9795Å, α=β= 90°, γ=120°, and the crystal has a non-centrosymmetric structure without phase transition, and niobium and tantalum jointly occupy the B site.
[0045] Specifically, due to Nb 5+ With Ta 5+ Belong to the same group of elements and have similar chemical structures, so in the crystal structure Ta 5+ The position is easily affected by Nb 5+ Replaced by niobium gallium silicate calcium tantalum, thus forming a single crystal (hereinafter referred to as CNTGS). At the same time, due to the different electron layers and radii of the two, Nb 5+ After entering the crystal lattice, the lattice parameters of the crystal will change. This change will further affect the high-temperature piezoelectric properties of the CNTGS crystal, giving the crystal unique advantages and potential application prospects in high-temperature piezoelectric applications.
[0046] The test results show that as the temperature rises, the electromechanical coupling coefficient of the undoped calcium tantalum gallium silicate crystal (hereinafter referred to as CTGS) increases from 10.95% to 12.45%, while the electromechanical coupling coefficient of the calcium tantalum gallium silicate crystal CNTGS increases from 11.25% to 12.96%. This increase in the electromechanical coupling coefficient indicates that the piezoelectric properties of CNTGS crystals at high temperatures are better than those of undoped CTGS crystals. At the same time, the resistivity of CNTGS crystals at high temperatures was tested and analyzed, and it was found that at 800°C, its resistivity was 2.23×10 7 Ω·cm, which is comparable to the resistivity of CTGS crystal (2.40×107 Ω·cm), which shows that it has excellent high-temperature resistivity. Therefore, CNTGS crystal is a crystal material with significant advantages in high-temperature piezoelectric applications, especially suitable for high-temperature piezoelectric sensors with operating temperatures exceeding 800 ℃.
[0047] In some embodiments, the relative dielectric constant of the crystalline material at room temperature is Greater than 18, relative dielectric constant Greater than 24.6, piezoelectric constant d 11 Greater than 4.2pC / N, electromechanical coupling coefficient at 600℃ k 12 Greater than 12.90%, resistivity greater than 2.20×10 at 800℃ 7 Ω·cm;
[0048] in, It represents the free dielectric constant of the 110 crystal plane in the X direction. represents the absolute dielectric constant, It represents the free dielectric constant of the 001 crystal plane in the Z direction.
[0049] In some embodiments, the piezoelectric constant of the calcium niobium tantalum gallium silicate piezoelectric crystal is d 11 Greater than 4.20pC / N, relative dielectric constant Greater than 18, relative dielectric constant Greater than 24.60; at a high temperature of 800°C, the resistivity of the crystal is greater than 2.20×10 7 Ω·cm, higher than 10 6 Ω·cm, indicating that CNTGS crystals have broad application prospects in high-temperature piezoelectric sensors with working temperatures exceeding 800℃.
[0050] The second aspect of the present invention provides a method for preparing a gallium niobium calcium tantalum silicate piezoelectric crystal material, wherein the gallium niobium calcium tantalum silicate piezoelectric crystal material is the gallium niobium calcium tantalum silicate piezoelectric crystal material according to any one of the first aspects above, and the preparation method comprises:
[0051] Step 1, preparing gallium niobium calcium tantalum silicate polycrystalline material;
[0052] Step 2, placing a calcium tantalum gallium silicate seed crystal at the bottom of the crucible, filling the polycrystalline material on top of the seed crystal and sealing the crucible;
[0053] Step 3, placing the crucible in a crystal growth furnace, raising the temperature in the crystal growth furnace to melt the polycrystalline material and the top of the seed crystal, completing the inoculation, and obtaining the inoculated material;
[0054] Step 4: Control the temperature gradient in the crystal growth furnace to decrease, so that the inoculated material is crystallized, kept warm, and cooled to obtain the gallium niobium tantalum calcium silicate piezoelectric crystal material.
[0055] In some embodiments, step 1 comprises:
[0056] Mixing CaCO3, Nb2O5, Ta2O5, Ga2O3 and SiO2 to obtain a mixed material;
[0057] The mixed material is sintered once at 1000° C. to 1100° C., and cooled to obtain a first sintered product;
[0058] The first sintering product is crushed, ground, and pressed into blocks, and a second sintering is performed at 1200° C. to 1350° C. and cooled to obtain the gallium niobium tantalum calcium silicate polycrystalline material.
[0059] In some embodiments, the first sintering time is 12 hours to 20 hours, and the second sintering time is 24 hours to 40 hours.
[0060] In some embodiments, step 3 comprises:
[0061] Placing the crucible in a crystal growth furnace, placing the portion of the crucible where the polycrystalline material is placed in the high temperature zone of the crystal growth furnace, and raising the temperature of the high temperature zone to a first melting temperature to melt the polycrystalline material to generate a polycrystalline material melt;
[0062] The portion of the crucible where the top of the seed crystal is placed is placed in the temperature gradient zone of the crystal growth furnace, and the temperature of the temperature gradient zone is raised to the second melting temperature to melt the top of the seed crystal, and the temperature is kept to complete the inoculation and obtain the inoculated material.
[0063] In some embodiments, the step of raising the temperature of the high temperature zone to a first melting temperature to melt the polycrystalline material and generate a polycrystalline material melt comprises: raising the temperature of the high temperature zone to 1480° C. to 1490° C. within 10 hours, so that the polycrystalline material is fully melted and overheated by 50° C. to 100° C., and keeping the temperature for 24 hours to 48 hours to melt the polycrystalline material and obtain a polycrystalline material melt;
[0064] The step of heating the temperature gradient zone to a second melting temperature to melt the top of the seed crystal, keeping the temperature, completing the inoculation, and obtaining the inoculated material comprises: heating the temperature gradient zone to 1380°C to 1390°C to melt the top of the seed crystal, keeping the temperature for 2 hours to 3 hours, completing the inoculation, and obtaining the inoculated material.
[0065] In some embodiments, step 4 includes:
[0066] The crucible is placed on the descending device of the crystal growth furnace, and the descending device is controlled to descend in the temperature gradient zone of the crystal growth furnace, so that the inoculated material in the molten state in the crucible is crystallized and then stops descending, heat preservation, and cooling to obtain the gallium niobium tantalum calcium silicate polycrystalline material.
[0067] In some embodiments, along the descending direction of the crucible, the temperature of the temperature gradient zone decreases according to a gradient of 30°C / cm to 50°C / cm, and the descending speed of the crucible is 6 mm / day to 10 mm / day;
[0068] The insulation condition is 1200°C to 1300°C for 1.0 hour to 2.0 hour;
[0069] The cooling condition is to gradually cool to room temperature at a rate of 30° C. / hour to 50° C. / hour.
[0070] In some embodiments, the chemical formula of the calcium tantalum gallium silicate seed crystal is Ca3TaGa3Si2O 14 Single crystal.
[0071] In some embodiments, the crucible may have a size of Φ9 × Φ25 × 100 mm.
[0072] The third aspect of the present invention provides a use of a gallium niobium calcium tantalum silicate piezoelectric crystal material, and the use of the gallium niobium calcium tantalum silicate piezoelectric crystal material in the preparation of piezoelectric crystal materials and sensor devices. The gallium niobium calcium tantalum silicate piezoelectric crystal material is a crystal material prepared by the preparation method of the gallium niobium calcium tantalum silicate piezoelectric crystal material described in any one of the first aspects or the gallium niobium calcium tantalum silicate piezoelectric crystal material described in any one of the second aspects.
[0073] Specifically, the method for preparing gallium niobium calcium tantalum silicate piezoelectric crystals of the present invention is a crucible descent method, which has the following characteristics:
[0074] (1) It can achieve crystal growth in non-growth habit directions and flexibly meet different application requirements;
[0075] (2) Supporting the growth of crystals of specific sizes by customizing the shape and size of the crucible;
[0076] (3) Use a closed crucible to effectively prevent external impurities from contaminating and volatilizing the melt components, ensuring crystal purity and chemical consistency;
[0077] (4) Multi-station crystal growth improves production efficiency, reduces costs, and enables mass production.
[0078] In some embodiments, the method specifically comprises:
[0079] (1) Ingredients:
[0080] The raw materials calcium carbonate (CaCO3), niobium oxide (Nb2O5), tantalum oxide (Ta2O5), gallium oxide (Ga2O3) and silicon dioxide (SiO2) were dried at 200°C and then quenched according to the chemical formula Ca3(Nb 0.2 Ta 0.8 )Ga3Si2O 14 The mass of each substance is weighed according to the stoichiometric ratio, and then fully mixed to obtain a mixed material:
[0081] (2) Preparation of polycrystalline materials:
[0082] The mixed material prepared in step (1) is placed in a muffle furnace, and is sintered for the first time in an environment at a temperature of 1000° C. to 1100° C. for 12 to 20 hours, and then cooled to room temperature to obtain a polycrystalline material after the first sintering; the polycrystalline material after the first sintering is crushed and ground to make it evenly mixed, pressed into a round cake-shaped material block, and is sintered for the second time at a temperature of 1200° C. to 1350° C. for 24 to 40 hours, and then cooled to room temperature to obtain a polycrystalline material of gallium niobium tantalum calcium silicate after the second sintering;
[0083] (3) Calcium gallium niobium tantalum silicate Ca3 (Nb 0.2 Ta 0.8 )Ga3Si2O 14 Single crystal growth:
[0084] The polycrystalline material and seed crystal obtained in step (2) are sealed in a platinum crucible of size 9 × 25 × 100 mm, wherein the seed crystal is located in the seed crystal well, and then the platinum crucible is placed in a corundum tube, and alumina powder is filled between the corundum tube and the platinum crucible to keep warm, and the corundum tube and the platinum crucible are placed in a furnace body. The corundum tube and the crucible containing the polycrystalline material are raised to the high temperature zone, and the program is set so that the temperature in the furnace body of the high temperature zone is slowly raised to 1480°C within 10 hours, so that the polycrystalline material is fully melted, and the melt is kept superheated at 50°C to 100°C, and kept warm for 24 hours to 48 hours to ensure that the polycrystalline material is fully melted and reaches a uniform state, so as to obtain a uniform high-temperature melt of the polycrystalline material.
[0085] The relative position of the crucible and the furnace body is adjusted so that the top of the seed crystal is located in the temperature gradient zone of the crystal growth furnace. The temperature of the top of the seed crystal in the temperature gradient zone is controlled within the range of 1380℃ ~ 1390℃ and maintained for 2 hours to complete the inoculation.
[0086] The platinum crucible is controlled to descend in the temperature gradient zone of the crystal growth furnace, so that the polycrystalline material in the crucible in a molten state gradually crystallizes in the temperature field as the crucible descends. During the crystal growth process, the temperature gradient of the temperature gradient zone is 30°C to 50°C / cm along the descending direction of the crucible, and the crucible is controlled to grow single crystals at a descending speed of 6 mm / day to 10 mm / day until all the polycrystalline material in the crucible is crystallized, and then the crucible is stopped from descending;
[0087] After the single crystal growth is completed, the crystal is maintained in the furnace temperature field at 1200℃ ~ 1300℃ and kept at a constant temperature for 1.0 hour ~ 2.0 hours, then cooled to room temperature at a rate of 30℃ / hour ~ 50℃ / hour, and the mechanical platform is lowered to take out the platinum crucible. After peeling off the platinum crucible, the gallium niobium tantalum calcium silicate piezoelectric crystal material is obtained.
[0088] The following is a further description in conjunction with specific embodiments and drawings.
[0089] Embodiment 1:
[0090] A method for preparing a gallium niobium calcium tantalum silicate piezoelectric crystal material, comprising:
[0091] (1) Ingredients
[0092] According to the chemical formula (Ca3(Nb 0.2 Ta 0.8 )Ga3Si2O 14 ), weigh raw materials calcium carbonate (CaCO3, 77.70 g, 0.78 mol), niobium oxide (Nb2O5, 6.05 g, 0.025 mol), tantalum oxide (Ta2O5, 45.74 g, 0.10 mol), gallium oxide (Ga2O3, 72.76 g, 0.39 mol) and silicon dioxide (SiO2, 31.10 g, 0.52 mol), then mix them well and dry them at 200°C to obtain a mixed material.
[0093] (2) Preparation of polycrystalline materials
[0094] The mixed material prepared in step (1) is placed in a muffle furnace, and sintered once at a constant temperature of 1100° C. for 12 hours, and cooled to room temperature to obtain a polycrystalline material after the first sintering; the polycrystalline material after the first sintering is crushed and ground to make it evenly mixed, pressed into a round cake-shaped material block, and sintered twice at a set temperature of 1350° C. and kept at a constant temperature for 24 hours, and cooled to room temperature to obtain a gallium niobium tantalum calcium silicate polycrystalline material after the second sintering.
[0095] (3) Ca3(Nb 0.2 Ta 0.8 )Ga3Si2O 14 Single crystal growth
[0096] The polycrystalline material and seed crystal obtained in step (2) are sealed in a platinum crucible with a size of 9 × 25 × 100 mm, wherein the seed crystal is located in the seed crystal well, and then the platinum crucible is placed in a corundum tube, and alumina powder is filled between the corundum tube and the platinum crucible to keep warm, and the corundum tube and the platinum crucible are placed in a furnace body. The corundum tube and the crucible containing the polycrystalline material are raised to the high temperature zone, and the program is set so that the temperature in the furnace body of the high temperature zone is slowly raised to 1480°C within 10 hours, so that the polycrystalline material is fully melted, and the melt is kept superheated at 100°C, and kept warm for 24 hours to ensure that the polycrystalline material is fully melted and reaches a uniform state, so as to obtain a uniform high-temperature melt of the polycrystalline material.
[0097] The relative position of the crucible and the furnace body was adjusted so that the top of the seed crystal was located in the temperature gradient zone of the crystal growth furnace. The temperature of the top of the seed crystal in the temperature gradient zone was controlled at 1380° C. and maintained for 2 hours to complete the seeding.
[0098] The platinum crucible is controlled to descend in the temperature gradient zone of the crystal growth furnace, so that the polycrystalline material in the crucible in a molten state gradually crystallizes in the temperature field as the crucible descends. During the crystal growth process, the temperature gradient of the temperature gradient zone is 50°C / cm along the descending direction of the crucible, and the crucible is controlled to grow a single crystal at a descending speed of 10 mm / day until all the polycrystalline material in the crucible is crystallized, and then the crucible is stopped from descending.
[0099] After the single crystal growth is completed, the crystal is kept in the furnace temperature field at 1300 ° C for 1.0 hour, then cooled to room temperature at a rate of 50 ° C / hour, and the mechanical platform is lowered to take out the platinum crucible. After the platinum crucible is peeled off, the gallium niobium tantalum calcium silicate piezoelectric crystal material ( Figure 1 ).
[0100] The crystals prepared in Example 1 were subjected to single crystal X-ray diffraction analysis and testing. Crystal samples of suitable size and regular shape were selected at 298K and single crystal phase determination was performed on a Bruker D8 X-ray powder diffractometer (Cu target, Kα radiation source, step size of 0.02). The experimental results of the test were obtained by processing the data with jade6.0 software, and the obtained X-ray diffraction pattern was compared with the standard card for analysis ( Figure 2 ). The results show that the grown crystals belong to the trigonal system, with a space group of P321 The crystal was cut into square pieces for dielectric properties testing. The relative dielectric constant at room temperature was It dropped from 18.04 to 17.00 at 380℃, and then increased from 17.00 to 17.37 in the temperature range of 380℃~530℃; and dropped to 17.01 in the temperature range of 530℃~600℃; the dielectric loss tanδ 11There is basically no loss from room temperature to 380℃, and it increases to 32.7% after 380℃; As the temperature rises, it continues to decrease from 24.63 to 21.31; the dielectric loss tanδ 33 In the range of 30℃~430℃, it remains at about 0% as the temperature rises; in the range of 430℃~600℃, it continues to increase and increases to 8.80% at 600℃. 5+ The addition of makes the elastic properties of CTGS crystals decrease, and the electromechanical coupling performance is k 12 It has increased from 11.25% at room temperature to 12.96% at 600℃ ( Figure 3 ), compared with the undoped CTGS crystal, the piezoelectric constant of the CNTGS crystal is comparable. The results show that Nb 5+ The addition of did not reduce the piezoelectric constant of the crystal. The resistivity at high temperature was evaluated using a crystal square with the (110) face of the crystal. It was found that at 800°C, the resistivity of the crystal was 2.23×10 7 Ω·cm( Figure 4 ), which is close to the CTGS crystal, and the activation energy of the crystal is calculated to be E a =1.12eV.
[0101] Embodiment 2:
[0102] A method for preparing a gallium niobium calcium tantalum silicate piezoelectric crystal material, comprising:
[0103] (1) Ingredients
[0104] According to the chemical formula (Ca3(Nb 0.2 Ta 0.8 )Ga3Si2O 14 ) in a stoichiometric ratio, weigh the raw materials calcium carbonate (CaCO3, 77.70 g, 0.78 mol), niobium oxide (Nb2O5, 6.05 g, 0.025 mol), tantalum oxide (Ta2O5, 45.74 g, 0.10 mol), gallium oxide (Ga2O3, 72.76 g, 0.39 mol) and silicon dioxide (SiO2, 31.10 g, 0.52 mol), then mix them well and dry them at 200 °C to obtain the mixed material:
[0105] (2) Preparation of polycrystalline materials
[0106] The mixed material prepared in step (1) is placed in a muffle furnace, and sintered once at a constant temperature of 1000° C. for 20 hours, and then cooled to room temperature to obtain a polycrystalline material after the first sintering; the polycrystalline material after the first sintering is crushed and ground to make it evenly mixed, pressed into a round cake-shaped material block, and sintered twice at a set temperature of 1200° C. and kept at the constant temperature for 40 hours, and then cooled to room temperature to obtain a gallium niobium tantalum calcium silicate polycrystalline material after the second sintering.
[0107] (3) Ca3(Nb 0.2 Ta 0.8 )Ga3Si2O 14 Single crystal growth
[0108] The polycrystalline material and seed crystal obtained in step (2) are sealed in a platinum crucible with a size of 9 × 25 × 100 mm, wherein the seed crystal is located in the seed crystal well, and then the platinum crucible is placed in a corundum tube, and alumina powder is filled between the corundum tube and the platinum crucible to keep warm, and the corundum tube and the platinum crucible are placed in a furnace body. The corundum tube and the crucible containing the polycrystalline material are raised to the high temperature zone, and the program is set so that the temperature in the furnace body of the high temperature zone is slowly raised to 1480°C within 10 hours, so that the polycrystalline material is fully melted, and the melt is kept superheated at 50°C, and kept warm for 48 hours to ensure that the polycrystalline material is fully melted and reaches a uniform state, so as to obtain a uniform high-temperature melt of the polycrystalline material.
[0109] The relative position of the crucible and the furnace body was adjusted so that the top of the seed crystal was located in the temperature gradient zone of the crystal growth furnace. The temperature of the top of the seed crystal in the temperature gradient zone was controlled at 1390° C. and maintained for 2 hours to complete the seeding.
[0110] The temperature in the crystal growth furnace is maintained at a constant 1480°C, and the platinum crucible is controlled to descend in the temperature gradient zone of the crystal growth furnace, so that the polycrystalline material in the crucible in a molten state gradually crystallizes in the temperature field as the crucible descends. During the crystal growth process, the temperature gradient in the temperature gradient zone is 30°C / cm along the direction of the crucible descent, and the crucible is controlled to grow single crystals at a descent rate of 6 mm / day until all the polycrystalline material in the crucible is crystallized, and then the crucible is stopped from descending;
[0111] After the single crystal growth is completed, the crystal is kept in the furnace temperature field at 1200 ° C for 2.0 hours, then cooled to room temperature at a rate of 30 ° C / hour, and the mechanical platform is lowered to take out the platinum crucible. After the platinum crucible is peeled off, the gallium niobium tantalum calcium silicate piezoelectric crystal material is obtained. The composition structure, piezoelectric properties and conductive properties of the material are then tested.
[0112] Embodiment 3:
[0113] A method for preparing a gallium niobium calcium tantalum silicate piezoelectric crystal material, comprising:
[0114] (1) Ingredients
[0115] According to the chemical formula (Ca3(Nb 0.2 Ta 0.8 )Ga3Si2O 14 ), weigh raw materials calcium carbonate (CaCO3, 77.70 g, 0.78 mol), niobium oxide (Nb2O5, 6.05 g, 0.025 mol), tantalum oxide (Ta2O5, 45.74 g, 0.10 mol), gallium oxide (Ga2O3, 72.76 g, 0.39 mol) and silicon dioxide (SiO2, 31.10 g, 0.52 mol), then mix them well and dry them at 200°C to obtain a mixed material.
[0116] (2) Preparation of polycrystalline materials
[0117] The mixed material prepared in step (1) is placed in a muffle furnace, and sintered once at a constant temperature of 1050° C. for 16 hours, and cooled to room temperature to obtain a polycrystalline material after the first sintering; the polycrystalline material after the first sintering is crushed and ground to make it evenly mixed, pressed into a round cake-shaped material block, and sintered twice at a set temperature of 1300° C. and kept at a constant temperature for 36 hours, and cooled to room temperature to obtain a gallium niobium tantalum calcium silicate polycrystalline material after the second sintering.
[0118] (3) Ca3(Nb 0.2 Ta 0.8 )Ga3Si2O 14 Single crystal growth
[0119] The polycrystalline material and seed crystal obtained in step (2) are sealed in a platinum crucible with a size of 9 × 25 × 100 mm, wherein the seed crystal is located in the seed crystal well, and then the platinum crucible is placed in a corundum tube, and alumina powder is filled between the corundum tube and the platinum crucible to keep warm, and the corundum tube and the platinum crucible are placed in a furnace body. The corundum tube and the crucible containing the polycrystalline material are raised to the high temperature zone, and the program is set so that the temperature in the furnace body of the high temperature zone is slowly raised to 1480°C within 10 hours, so that the polycrystalline material is fully melted, and the melt is kept superheated at 80°C, and kept warm for 36 hours to ensure that the polycrystalline material is fully melted and reaches a uniform state, so as to obtain a uniform high-temperature melt of the polycrystalline material.
[0120] The relative position of the crucible and the furnace body was adjusted so that the top of the seed crystal was located in the temperature gradient zone of the crystal growth furnace. The temperature of the top of the seed crystal in the temperature gradient zone was controlled at 1385° C. and maintained for 2 hours to complete the seeding.
[0121] The temperature in the crystal growth furnace is maintained at a constant 1480°C, and the platinum crucible is controlled to descend in the temperature gradient zone of the crystal growth furnace, so that the polycrystalline material in the crucible in a molten state gradually crystallizes in the temperature field as the crucible descends. During the crystal growth process, the temperature gradient in the temperature gradient zone is 40°C / cm along the direction of the crucible descent, and the crucible is controlled to grow single crystals at a descent rate of 8 mm / day until all the polycrystalline material in the crucible is crystallized, and then the crucible is stopped from descending;
[0122] After the single crystal growth is completed, the crystal is kept in the furnace temperature field at 1250℃ for 2.0 hours, then cooled to room temperature at a rate of 40℃ / hour, and the mechanical platform is lowered to take out the platinum crucible. After the platinum crucible is peeled off, the gallium niobium tantalum calcium silicate piezoelectric crystal material is obtained. The composition structure, piezoelectric properties and conductive properties of the material are then tested.
Claims
1. A gallium niobium calcium tantalum silicate piezoelectric crystal material, characterized in that: The chemical formula of the calcium gallium niobium tantalum silicate piezoelectric crystal is Ca3(Nb 0.2 Ta 0.8 )Ga3Si2O 14 , the crystal belongs to A3BC3D2O 14 The invention relates to a tantalum-based tantalum crystal of the present invention. The space group of the crystal is P321. The unit cell parameters of the crystal are a = b = 8.1020 Å~8.1025 Å, c = 4.9785 Å~4.9795 Å, α=β=90°, γ=120°, and the crystal has a non-centrosymmetric structure without phase transition, and niobium and tantalum jointly occupy the B site.
2. The piezoelectric crystal material of gallium niobium calcium tantalum silicate according to claim 1, characterized in that: The relative dielectric constant of the crystal material at room temperature Greater than 18, relative dielectric constant Greater than 24.6, piezoelectric constant d 11 Greater than 4.2pC / N, electromechanical coupling coefficient at 600℃ k 12 Greater than 12.9%, resistivity greater than 2.2×10 at 800℃ 7 Ω·cm; in, It represents the free dielectric constant of the 110 crystal plane in the X direction. represents the absolute dielectric constant, It represents the free dielectric constant of the 001 crystal plane in the Z direction.
3. A method for preparing gallium niobium tantalum calcium silicate piezoelectric crystal material, characterized in that: The gallium niobium tantalum calcium silicate piezoelectric crystal material is the gallium niobium tantalum calcium silicate piezoelectric crystal material according to any one of claims 1 to 2, and the preparation method comprises: Step 1, preparing gallium niobium calcium tantalum silicate polycrystalline material; Step 2, placing a calcium tantalum gallium silicate seed crystal at the bottom of the crucible, filling the polycrystalline material on top of the seed crystal and sealing the crucible; Step 3, placing the crucible in a crystal growth furnace, raising the temperature in the crystal growth furnace to melt the polycrystalline material and the top of the seed crystal, completing the inoculation, and obtaining the inoculated material; Step 4: Control the temperature gradient in the crystal growth furnace to decrease, so that the inoculated material is crystallized, kept warm, and cooled to obtain the gallium niobium tantalum calcium silicate piezoelectric crystal material.
4. The preparation method according to claim 3, characterized in that: The step 1 comprises: Mixing CaCO3, Nb2O5, Ta2O5, Ga2O3 and SiO2 to obtain a mixed material; The mixed material is sintered once at 1000° C. to 1100° C., and cooled to obtain a first sintered product; The first sintering product is crushed, ground, and pressed into blocks, and a second sintering is performed at 1200° C. to 1350° C. and cooled to obtain the gallium niobium tantalum calcium silicate polycrystalline material.
5. The preparation method according to claim 4, characterized in that: The first sintering time is 12 hours to 20 hours, and the second sintering time is 24 hours to 40 hours.
6. The preparation method according to claim 3, characterized in that: The step 3 comprises: Placing the crucible in a crystal growth furnace, placing the portion of the crucible where the polycrystalline material is placed in the high temperature zone of the crystal growth furnace, and raising the temperature of the high temperature zone to a first melting temperature to melt the polycrystalline material to generate a polycrystalline material melt; The portion of the crucible where the top of the seed crystal is placed is placed in the temperature gradient zone of the crystal growth furnace, and the temperature of the temperature gradient zone is raised to the second melting temperature to melt the top of the seed crystal, and the temperature is kept to complete the inoculation and obtain the inoculated material.
7. The preparation method according to claim 6, characterized in that: The step of raising the temperature of the high temperature zone to a first melting temperature to melt the polycrystalline material and generate a polycrystalline material melt comprises: raising the temperature of the high temperature zone to 1480° C. to 1490° C. within 10 hours to fully melt the polycrystalline material and overheating the polycrystalline material by 50° C. to 100° C., and keeping the temperature for 24 hours to 48 hours to melt the polycrystalline material and obtain a polycrystalline material melt; The step of heating the temperature gradient zone to a second melting temperature to melt the top of the seed crystal, keeping the temperature, completing the inoculation, and obtaining the inoculated material comprises: heating the temperature gradient zone to 1380°C to 1390°C to melt the top of the seed crystal, keeping the temperature for 2 hours to 3 hours, completing the inoculation, and obtaining the inoculated material.
8. The preparation method according to claim 3, characterized in that: The step 4 comprises: The crucible is placed on the descending device of the crystal growth furnace, and the descending device is controlled to descend in the temperature gradient zone of the crystal growth furnace, so that the inoculated material in the molten state in the crucible is crystallized and then stops descending, heat preservation, and cooling to obtain the gallium niobium tantalum calcium silicate polycrystalline material.
9. The preparation method according to claim 8, characterized in that: Along the descending direction of the crucible, the temperature of the temperature gradient zone decreases according to a gradient of 30°C / cm to 50°C / cm, and the descending speed of the crucible is 6mm / day to 10mm / day; The insulation condition is 1200°C to 1300°C for 1.0 hour to 2.0 hour; The cooling condition is to gradually cool to room temperature at a rate of 30° C. / hour to 50° C. / hour.
10. A use of a gallium niobium calcium tantalum silicate piezoelectric crystal material, characterized in that: The gallium niobium tantalum calcium silicate piezoelectric crystal material is used in the preparation of piezoelectric crystal materials and sensor devices. The gallium niobium tantalum calcium silicate piezoelectric crystal material is the gallium niobium tantalum calcium silicate piezoelectric crystal material described in any one of claims 1 to 2 or a crystal material prepared by the preparation method of the gallium niobium tantalum calcium silicate piezoelectric crystal material described in any one of claims 3 to 9.
Citation Information
Patent Citations
Aluminum-gallium-niobium-calcium silicate piezo-electric crystal and preparation method thereof
CN104695017A
Aluminum gallium tantalum calcium silicate piezoelectric crystal and preparing method thereof
CN104695018A